Lighting Improvement and Space Flexibility using Moveable Walls - Sita Yuliastuti Amijaya (Journal of Architectural Research and Design Studies, 2021)
This article discusses design of possible connection system by moving the vertical and horizontal construction’ elements. The vertical and horizontal elements are applied to ensure comfortable indoor lighting comfort. This idea is part of sustainable low-technology strategy. The developed mobile facade technology aims to transmit sunlight into the space unimpeded, as well as to improve the building’ performance. This research is preliminary part of the design development in producing flexible space using movable wall and also the need to control sunlight by using dynamic facades. The research method uses application of modeling to create the desired shapes and prototypes for movement design. Applying multiple movable joints and various vertical or horizontal elements will improve lighting conditions. In addition, the application of a movable wall system into design can increase the indoor comfort without reducing the room function.Keywords: dynamic facades; indoor comfort; lighting improvement, moveable walls; space flexibility